Entrance of above-ground root cellar, Keels - Catherwood, Kristin (2012)
Exterior photo of entrance wooden root cellar on the east side of Keels. NL. Unknown date of construction. Style of cellar can be contrasted with other cellar types in Keels. The entrance is located on the south side of the building. Note the horseshoe affixed to the door. Horseshoes are found on several buildings in Keels, both houses and outbuildings.